2019
DOI: 10.3390/ijms20030661
|View full text |Cite
|
Sign up to set email alerts
|

GeneLab Database Analyses Suggest Long-Term Impact of Space Radiation on the Cardiovascular System by the Activation of FYN Through Reactive Oxygen Species

Abstract: Space radiation has recently been considered a risk factor for astronauts’ cardiac health. As an example, for the case of how to query and identify datasets within NASA’s GeneLab database and demonstrate the database utility, we used an unbiased systems biology method for identifying key genes/drivers for the contribution of space radiation on the cardiovascular system. This knowledge can contribute to designing appropriate experiments targeting these specific pathways. Microarray data from cardiomyocytes of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 84 publications
0
25
0
Order By: Relevance
“…Finally, we performed pathway analysis utilizing the miRNAseq data with C2 curated gene sets from MSigDB on the miRNA-seq data and displayed all significantly regulated pathways ( Figure 3G) for the liver and soleus muscle. Data for the plasma and heart tissues are in companion papers and show similar results (Paul et al, 2020;Wuu et al, 2020), and the pathways that showed suppression (false discovery rate [FDR]adjusted p value < 0.25; Figure 3G) have been previously implicated in cardiovascular adaptations to spaceflight (Beheshti et al, 2018(Beheshti et al, , 2019. These specific pathways were selected for the countermeasure experiments (below).…”
Section: Predicted Spaceflight Mirna Signature In Rodents Was Validatmentioning
confidence: 87%
“…Finally, we performed pathway analysis utilizing the miRNAseq data with C2 curated gene sets from MSigDB on the miRNA-seq data and displayed all significantly regulated pathways ( Figure 3G) for the liver and soleus muscle. Data for the plasma and heart tissues are in companion papers and show similar results (Paul et al, 2020;Wuu et al, 2020), and the pathways that showed suppression (false discovery rate [FDR]adjusted p value < 0.25; Figure 3G) have been previously implicated in cardiovascular adaptations to spaceflight (Beheshti et al, 2018(Beheshti et al, , 2019. These specific pathways were selected for the countermeasure experiments (below).…”
Section: Predicted Spaceflight Mirna Signature In Rodents Was Validatmentioning
confidence: 87%
“…Accumulated knowledge over years of research on the biological effects of radiation points toward the development of holistic approaches to “big data” analysis by employing systems biology methodologies (Unger, 2014 ; Beheshti et al, 2019 ; Spratt and Speers, 2019 ; Kanakoglou et al, 2020 ). Herein, we employed a rigorous systems biology approach to unravel the molecular determinants of resistance of cancer cells to IR, based solely on HTP data.…”
Section: Introductionmentioning
confidence: 99%
“…Fyn has a pathological signaling role during inflammatory bowel disorders ( Ban et al, 2008 ; Saksena et al, 2008 ). Fyn is also upregulated during ROS-induced signaling in the cardiovascular system ( Beheshti et al, 2019 ). The loss of central nervous system progenitor cells upon exposure to pro-oxidative insults underscores Fyn’s degenerative roles ( Abe and Berk, 1999 ; Sanguinetti et al, 2003 ; Frossi et al, 2007 ; Li et al, 2007 ; Ban et al, 2008 ; Saksena et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%